PENEGAKAN HUKUM PIDANA TERHADAP PELANGGARAN KAWASAN TANPA ROKOK BERDASARKAN UNDANG-UNDANG NO. 17 TAHUN 2023 TENTANG KESEHATAN - Daeng, Yusuf; Abdurachman, Irwan; Haidar Muhammad Bagir, A.; Mustafa, Hari; Noviarti, Dini (Universitas Pahlawan, 2023)
Article 150, Article 151 and Article 152 of Law no. 17 of 2023 concerning Health. The smoke-free area policy is regulated in Article 150 and Article 152 of Law no. 17 of 2023 concerning Health. Furthermore, Article 437 paragraph (2) of the Health Law has formulated the threat of a criminal fine with a maximum amount of Rp. 50,000,000,- (fifty million rupiah). However, the existence of these laws and regulations has not caused the number of smokers in Indonesia to decrease. In fact, in the last 10 (ten) years the number of adult smokers in Indonesia has increased quite high. Based on the results of the 2021 Global Adult Tobacco Survey (GATS) launched by the Ministry of Health, it shows that the number of adult smokers has increased by 8.8 million people from previously 60.3 million people in 2011 to 69.1% in 2021. This research descriptive in nature with a normative juridical approach. Data was collected through literature study. Then it is analyzed qualitatively and presented descriptively analytically. Based on the discussion above, it can be concluded that law enforcement for violators of non-smoking areas in Indonesia is still low. In fact, it is not an exaggeration that law enforcement against violators of non-smoking areas is not actually working. There are 3 (three) factors that hinder law enforcement for non-smoking zone violators, namely: first, legal substance factors/legal factors that do not clearly and firmly regulate the mechanism for implementing criminal sanctions against violators. Second, the legal structure/law enforcement factor does not understand the procedures for taking action against violations as regulated in the Criminal Procedure Code. Third, the legal culture factor of society which often violates the law on the one hand and the bad law enforcement culture of law enforcement officials on the other hand, the high smoking habit of Indonesian society, and even the law enforcers themselves often commit violations in non-smoking areas. The existence of cigarettes as one of the country's biggest sources of income means that the state is half-hearted in enforcing the law. Community cultures and entrepreneurs who often use cigarettes as sponsors in various events and activities make law enforcement difficult.